1998
DOI: 10.1007/s004310050965
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of patients with upper airway obstruction transported to a regional paediatric intensive care unit

Abstract: Although viral croup remains the most common diagnostic category presenting at the DGH level with severe UAO, a wide range of other diagnoses is seen. Despite clear evidence of benefit, steroid administration to children presenting at the DGH with viral croup has not become routine practice. Once intubated, no reliable predictors of successful extubation were found amongst this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
4
3
Order By: Relevance
“…It has even been described as a disease unknown to this part of the world, although Hib‐associated meningitis and pneumonia are well recognized in children of the region 12,13 . Viral croup, although the most common infective cause for severe upper airway obstruction in our study population, appeared less important when compared with the experiences reported by PICU of developed temperate nations 1,14 . More importantly, the intubation rate of 17% seen in our study population is much lower than the 40–75% encountered in these PICU 1,14 .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It has even been described as a disease unknown to this part of the world, although Hib‐associated meningitis and pneumonia are well recognized in children of the region 12,13 . Viral croup, although the most common infective cause for severe upper airway obstruction in our study population, appeared less important when compared with the experiences reported by PICU of developed temperate nations 1,14 . More importantly, the intubation rate of 17% seen in our study population is much lower than the 40–75% encountered in these PICU 1,14 .…”
Section: Discussioncontrasting
confidence: 63%
“…It requires urgent management by clinicians skilled and familiar in successfully securing a patent airway to avoid a potentially rapid fatal outcome. The diagnostic categories requiring intensive care in developed nations are heterogeneous with viral croup, the predominant cause for admission for life‐threatening upper airway obstruction 1,2 . However, life‐threatening upper airway obstruction encountered in children of the developing nations and the tropics, in particular, has not been extensively documented.…”
mentioning
confidence: 99%
“…The supraglottic anatomy and vocal cords should be easy to identify, but the subglottis and trachea will be narrowed and a smaller size of tracheal tube should be selected. Intubation should be straightforward, but the presence of preexisting subglottic stenosis, which exacerbates symptoms, may be a risk factor for difficult intubation [11]. Following intubation, the tracheal tube should be secured and the child allowed to emerge from anaesthesia.…”
Section: Croupmentioning
confidence: 99%
“…Tracheal intubation within the first hour of presentation is only required in the minority of cases; thus there may be time for adequate assessment and for steroid therapy to take effect [11].…”
Section: Croupmentioning
confidence: 99%
See 1 more Smart Citation